Expression of NDRG2 in human lung cancer and its correlation with prognosis - Li, Shu-jun (Springer US, 2013)
We had reported that N-myc downstream–regulated gene (NDRG2) regulates colorectal cancer, breast cancer, clear cell renal cell carcinoma, pancreatic cancer, thyroid cancer and esophageal squamous cell proliferation, development, and apoptosis. The goal of this study was to determine the expression pattern of NDRG2 in human lung cancer and its correlation with prognosis. Immunohistochemistry, RT-PCR and western blot were used to explore the expression of NDRG2 in 185 human lung cancer patients. The correlation of NDRG2 expression with patients’ survival rate was assessed by Kaplan–Meier and Cox regression. Results showed that the expression level of NDRG2 was decreased in human lung cancer tissues, and NDRG2 was positively correlated with depth of invasion (P = 0.038), vascular invasion (P = 0.036), tumor grade (P = 0.039), and tumor size (P = 0.026). Both RT-PCR and Western blots demonstrated that NDRG2 mRNA and protein levels were lower in lung cancer compared to the adjacent normal tissue from the same individual, and NDRG2 level was negatively correlated with UICC stage. Additionally, survival time of lung cancer patients with high expression of NDRG2 was longer than those with low expression during the 5-year follow-up period (P = 0.001). Meanwhile, COX regression analysis indicated that low expression of NDRG2, ≥pT(3), pM(1), ≥pN(1) and vascular invasion were independent, poor prognostic factors of lung cancer patients. These data showed that NDRG2 may play an important role in human lung cancer tumourigenesis, and NDRG2 might serve as a novel prognostic marker in human lung cancer.